Rice Straw as a Source of Nanocellulose for Sustainable Food Packaging Materials: A Review - Makdud Islam; Praveen Saini; Rahul Das; Shubhra Shekhar; Akhouri Sanjay Kumar Sinha; Kamlesh Prasad (BioResources, 2023)
Asian countries, despite being the largest producers and yielding a significant proportion of the world’s rice, have poor disposal facilities for the harvested rice straw (stubble). Due to higher costs in their handling relative to their value, local farmers prefer the burning of stubble fields, thus creating environmental problems. Even though the government has taken initiatives, no effective solution has been discovered to handle this large agro-waste problem efficiently. In this regard, the utilization of rice straw to develop nanocellulose (NC) products is of interest. Renewability and biodegradability, along with suitable mechanical and thermal properties required for the packaging functions, are key advantages of NC. The bio-nanocomposites prepared using NC and other bio-based polymers are also being widely considered for sustainable food packaging applications due to the reinforcement provided by NC and alternative petroleum-based packaging materials. This review provides an overview of process utilization for preparing NC products using rice straw, pulping methods, and isolation to produce bio-nanocomposites for sustainable food packaging applications. The challenges and future aspects covering the utilization of rice straw for producing NC and eventually producing active packaging materials are also discussed.